Synthesis and Property Study of N,N-Dithiocarboxy Diethylenetriamine Ethyl Polymer - Zheng, H.L.; Xiang, X.Y.; Tan, M.Z.; Zhu, G.C.; He, Q.; Ma, J.Y. (Asian Journal of Chemistry, 2012)
In this research, the synthesis and property of N,N-dithiocarboxy diethylenetriamine ethyl polymer were investigated. The polymer was synthesized through one-step reaction of diethylenetriamine, carbon disulfide with 1,2-dichloroethane, with the reaction time and required temperature being reduced significantly compared with that of traditional two-step reaction. Such factors as addition of sodium-hydroxide and its adding procedure, adding procedure of carbon disulfide, addition of diethylenetriamine, reaction temperature and reaction time were studied in details. Physical and chemical characteristics of this polymer were determined taking advantage of IR, UV and melting point test. Heavy-metal-ion absorbing property of this polymer was studied intensively. The results showed that several kinds of heavy metal ions could be significantly absorbed with the produced polymer, among which Ag+, Cu2+ and Zn2+ could be absorbed most effectively. The absorption ability of this polymer was maximized when the pH value was controlled at 5.